Electronic correlations in a two-level dimer - Macedo Jr., Lazaro A.; Lagos, Roberto E. [UNESP] (Elsevier, 2001)
The exact solution for the full electronic Hamiltonian for a two-level dimer is obtained. The parameter constellation (roughly 20) is reparametrized via orthogonal Gaussian atomic orbitals, yielding a five-parameter model. With the dimer embedded in a thermal bath, the specific heat and several temperature-dependent dynamical susceptibilities are computed. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Correlated electron system; Dynamic susceptibility